Makna Simbolik Nilai Feminisme Tokoh Nyai Ontosoroh dalam Novel Bumi Manusia Karya Pramoedya Ananta Toer - Shafa Tasya Amanda; Faizal Hamzah Lubis (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
The feminist movement is a movement of women to reject everything that tries to marginalize and demean the dominant culture, both in the political, economic, and other social fields. By Pramoedya Ananta Toer, the story of a nyai is portrayed through the character Nyai Ontosoroh in the novel Bumi Manusia. Pramoedya describes, Nyai Ontosoroh is not just a nyai who is only a sexual object and the colonial master's social prestige. Nyai Ontosoroh presents herself as no longer just a concubine, a pet, and a display for her master. Likewise, the obnoxious nature attached to the nyai was denied by him. Nyai Ontosoroh transformed herself into a different nyai. The formulation of the problem in this writing is what is the symbolic meaning of the feminism value of the character Nyai Ontosoroh in Pramoedya Ananta Toer's novel Bumi Manusia? The purpose of this paper is to find out the symbolic meaning of the feminist value of the character Nyai Ontosoroh in the novel Bumi Manusia by Pramoedya Ananta Toer. The research method used is a qualitative research method with the semiotic analysis technique of Ferdinand de Saussure. The depiction of the character Nyai Ontosoroh in the novel Bumi Manusia is very thick with feminism values, where there are elements of freedom, power, and justice in it.